The Global Availability of Rabies Immune Globulin and Rabies Vaccine in Clinics Providing Direct Care to Travelers1. Issue 3 (14th March 2013) - Jentes, Emily S.; Blanton, Jesse D.; Johnson, Katherine J.; Petersen, Brett W.; Lamias, Mark J.; Robertson, Kis; Franka, Richard; Briggs, Deborah; Costa, Peter; Lai, Irene; Quarry, Doug; Rupprecht, Charles E.; et al.
Abstract : Background: Rabies, which is globally endemic, poses a risk to international travelers. To improve recommendations for travelers, we assessed the global availability of rabies vaccine (RV) and rabies immune globulin (RIG). Methods: We conducted a 20‐question online survey, in English, Spanish, and French, distributed via e‐mail to travel medicine providers and other clinicians worldwide from February 1 to March 30, 2011. Results were compiled according to the region. Results: Among total respondents, only 190 indicated that they provided traveler postexposure care. Most responses came from North America (38%), Western Europe (19%), Australia and South and West Pacific Islands (11%), East and Southeast Asia (8%), and Southern Africa (6%). Approximately one third of 187 respondents stated that patients presented with wounds from an animal exposure that were seldom or never adequately cleansed. RIG was often or always accessible for 100% ( n  = 5) of respondents in the Middle East and North Africa; 94% ( n  = 17) in Australia and South and West Pacific Islands; 20% ( n  = 1) in Tropical South America; and 56% ( n  = 5) in Eastern Europe and Northern Asia. Ninety‐one percent ( n  = 158) of all respondents reported that RV was often or always accessible. For all regions, 35% ( n  = 58) and 26% ( n  = 43) of respondents felt that the cost was too high for RIG and RV, respectively. Conclusion: The availability of RV and RIG varied by geographic region. All travelers should be informed that RIG and RV might not be readily available at their destination and that travel health and medical evacuation insurance should be considered prior to departure. Travelers should be educated to avoid animal exposures; to clean all animal bites, licks, and scratches thoroughly with soap and water; and to seek medical care immediately, even if overseas.